Meningitis as an Initial Presentation of COVID-19: A Case Report - Naz, Sidra; Hanif, Muhammad; Haider, Muhammad Adnan; Ali, Mukarram Jamat; Ahmed, Muhammad Umer; Saleem, Sana (Frontiers in Public Health, 2020)
The common presenting symptoms of fever, fatigue, and mild respiratory symptoms like dry cough, are associated with COVID-19, however, patients can also develop neurological manifestations like headache, anosmia, hyposmia, dysgeusia, meningitis, encephalitis, and acute cerebrovascular accidents during the disease. Although very rare, these neurological manifestations are sometimes the sole initial presenting complaint of COVID-19. This case report discusses patients where the initial presenting symptoms seemed to be exclusive to meningitis but the later diagnosis was COVID-19. It is important to increase awareness of these rare presentations in physicians and healthcare workers and facilitate early diagnosis and management to prevent the horizontal spread of the disease.